Surface Sediment Diatom as A Water Quality Indicator: Case Study: Cilalay and Cibuntu Ponds, Cibinong - Aan Dianto; Taofik Jasalesmana; Luki Subehi; Ahmad Yusuf Afandi; Ardo Ramdhani (Indonesian Journal of Limnology, 2020)
Diatom is classified as algae within the Division of Bacillariophyta. They are unicellular eukaryotic organisms characterized by siliceous cell walls that can be long preserved in sediments. Therefore, diatom analysis in sediment records is a potential water quality indicator for present or paleo studies. The current knowledge on the distribution and diversity of diatoms in the sediment in the urban pond is poorly known. This study aimed to identify the distribution and diversity of diatoms from the sediments of the pond. We expect to obtain a primary database of a variety of diatoms. The sediment samples were taken from Cibuntu and Cilalay Ponds in Cibinong Botanical Garden. Sediments were digested using HCL and H2O2. The resulting diatom solution was dried and transferred onto glass coverslip, which subsequently mounted onto microscope slides using Naphrax (Refraction index 1.7). Diatom identification was examined using a light microscope at 1,000x magnification. Diatom communities in Cibuntu Pond were dominated by species Aulacoseria ambigua, Eunotia bilunaris, Cymbopleura sp, Discostella stelligera, and Rossithidium sp with diversity index of 2.4 and species evenness of 0.8. Whereas, species Fragilaria sp, Eunotia monodon, Navicymbula pusilla, Eunotia bilunaris, and Pinnularia viridis were predominant in Cilalay Pond with diversity index of 1.6 and species evenness of 0.5. Based on the diatom community, Cibuntu Pond is eutrophic indicated by the occurrence of Aulacoseria ambigua, whereas Cilalay Pond is meso-eutrophic indicated by the dominance of Fragillaria. This exploratory survey provides the first inventory of diatom assemblage in Cibuntu and Cilalay Ponds for roughly inferring the environmental changes in a shallow lake ecosystem.